Applying sensory modulation to mental health inpatient care to reduce seclusion and restraint: a case control study. (3rd October 2017) - Andersen, Charlotte; Kolmos, Anne; Andersen, Kjeld; Sippel, Volkmar; Stenager, Elsebeth
Abstract: Background: Clinical training in managing conflicts and preventing violence seldom contains sensory modulation (SM) as a method to de-escalate and prevent restraint and seclusion. Sensory-based interventions promote adaptive regulation of arousal and emotion. SM is a complementary approach that is associated with reduced rates of seclusion and restraint in mental healthcare, but there is need for more research in this area. Aims: Using SM to reduce restraint and seclusion in inpatient mental health care. Methods: The study included two similar psychiatric units where one unit implemented SM and one unit served as the control group. In the very beginning of the study, a staff-training program in the use of SM including assessment tools and intervention strategies was established. Data on restraint and forced medicine were sampled post the course of the year of implementation and compared with the control group. Results: The use of belts decreased with 38% compared to the control group. The use of forced medication decreased with 46% compared to the control group. Altogether the use of physical restraint and forced medication decreased significantly with 42% ( p  < .05). Conclusions: Implementing a SM approach in mental healthcare facilities has a significant effect on the reduction of restraint and seclusion. As a part of the implementation, staff training and education in SM are crucial.